THE INTERACTIVE BRAND EXPERIENCE AND ITS IMPACT ON CUSTOMER CITIZENSHIP BEHAVIOR - Samer Abdulhussen Kahyoosh Al Jawhari (Scholar Express Journals, 2025)
This research aims at examining the impact of Interactive Brand Experience on customer’s citizenship behavior by addressing the following question: (What is the impact of Interactive Brand Experience on the customer’s citizenship behavior). The researcher employed a descriptive and inferential approach to describe the study sample, analyze responses, and test hypotheses based on the outputs of both programs (SPSS.V26). A total of 400 questionnaires were distributed, with 380 valid responses used for analysis. The results show significant statistical evidence supporting the main hypotheses regarding the influence of Interactive Brand Experience on customer’s citizenship behavior. Particularly, the dimension of "helping and assisting others" emerges as central to customer’s citizenship behavior; the reason is that Xiaomi's senior management prioritizes the development of technical skills, creating enjoyable customer experiences, and employing frontline personnel with extensive professional expertise, which are considered critical factors for achieving success
Keywords: Interactive Brand Experience; customer’s citizenship behavior; recommendations and proposals